A new species of the genus Stiphodon from Palawan, Philippines (Gobiidae: Sicydiinae) - Maeda, Ken; Palla, Herminie P. (Zootaxa, 2015)
Palawan is an island in the western Philippines, and the freshwater fish fauna of this island has received limited research attention. In the present study, a new goby species, Stiphodon palawanensis, is described on the basis of 57 specimens collected from freshwater streams on the island. This species can be distinguished from its congeners by having nine segmented rays in the second dorsal fin, 15 rays in the pectoral fin, a pointed first dorsal fin in males, premaxilla with 45–71 tricuspid teeth, the nape and posterior half of the occipital region covered by cycloid scales, 9–11 dusky transverse bars laterally on the trunk and tail, a line of black blotches (in male) or a black band (in female) on the distal part of the second dorsal fin, and the first dorsal and pectoral fins lacking distinctive markings. The new species has been found only on the Sulu Sea side of central Palawan. Three congeners, S. percnopterygionus, S. atropurpureus, and S. pulchellus have also been recorded from Palawan.